2021
DOI: 10.1038/s41420-021-00603-z
|View full text |Cite
|
Sign up to set email alerts
|

LIF/LIFR oncogenic signaling is a novel therapeutic target in endometrial cancer

Abstract: Endometrial cancer (EC) is the fourth most common cancer in women. Advanced-stage EC has limited treatment options with a poor prognosis. There is an unmet need for the identification of actionable drivers for the development of targeted therapies in EC. Leukemia inhibitory factor receptor (LIFR) and its ligand LIF play a major role in cancer progression, metastasis, stemness, and therapy resistance. However, little is known about the functional significance of the LIF/LIFR axis in EC progression. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Some of the defined target genes of LMNB1 like LIFR and IL6R are already reported to be cancer associated [ 60 , 61 ]. LIFR belongs to the type I cytokine receptor family and could form a receptor complex which is involved in important cellular processes like differentiation, proliferation, and survival [ 62 ]. The LIF/LIFR axis is reported to be involved in the maintenance of stem cells [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the defined target genes of LMNB1 like LIFR and IL6R are already reported to be cancer associated [ 60 , 61 ]. LIFR belongs to the type I cytokine receptor family and could form a receptor complex which is involved in important cellular processes like differentiation, proliferation, and survival [ 62 ]. The LIF/LIFR axis is reported to be involved in the maintenance of stem cells [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…LIFR belongs to the type I cytokine receptor family and could form a receptor complex which is involved in important cellular processes like differentiation, proliferation, and survival [ 62 ]. The LIF/LIFR axis is reported to be involved in the maintenance of stem cells [ 62 ]. Maybe the loss of LIFR due to LMNB1 knockdown results in reduction of the stemness like properties of melanoma cells leading to senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Human EC cell lines HEC-1-A, AN3 CA and RL95-2 were purchased from the American Type Culture Collection (ATCC, Manassas, VA, USA) and cultured as described [ 16 ]. Ishikawa cells were purchased from Sigma (Millipore Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It is involved in maintaining hepatocyte pluripotency, protecting the liver, promoting glucose absorption and utilization, regulating cellular proliferation and differentiation, and other biological processes. Studies have reported that LIFR activates the JAK/STAT, ERK/MAPK, and Akt/PI3K pathways in tumor formation, inflammation, and cardiac function [ 15 17 ]. Woosley, et al found that ILEI forms a ligand-receptor complex by binding to the extracellular binding factor region of LIFR [ 18 ], suggesting that LIFR may be a key downstream effector molecule for many functions of ILEI.…”
Section: Introductionmentioning
confidence: 99%